2018
DOI: 10.1117/1.nph.5.2.025007
|View full text |Cite
|
Sign up to set email alerts
|

Using a simulation approach to optimize time-domain diffuse correlation spectroscopy measurement on human head

Abstract: Time-domain diffuse correlation spectroscopy (TD-DCS) has been recently proposed to improve detection of deep blood flow dynamics in a biological tissue, such as human brain. To obtain a high sensitive measurement, several experimental parameters such as the source-detector (SD) distance, gate opening time, and width need to be considered and optimized. We use a simulation approach to optimize these parameters based on Monte Carlo computations using a realistic human head model. Two cortical regions are invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
0
15
1
Order By: Relevance
“…31,32 Although TR detection has also been proposed for DCS, 33 neuromonitoring applications of this approach are challenging due to the poorer signal-to-noise ratio (SNR) of current technology. 34 However, the substantially higher blood flow in the brain compared with the scalp gives DCS an inherent advantage in terms of depth sensitivity compared with CW NIRS. 15 Studies involving tissue-mimicking phantoms, animal models, and human applications have shown that scalp and CBF can be separated using multilayered analytical models to analyze DCS data collected at different source-detector separations.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Although TR detection has also been proposed for DCS, 33 neuromonitoring applications of this approach are challenging due to the poorer signal-to-noise ratio (SNR) of current technology. 34 However, the substantially higher blood flow in the brain compared with the scalp gives DCS an inherent advantage in terms of depth sensitivity compared with CW NIRS. 15 Studies involving tissue-mimicking phantoms, animal models, and human applications have shown that scalp and CBF can be separated using multilayered analytical models to analyze DCS data collected at different source-detector separations.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, TD-DCS can provide higher sensitivity detection for deep dynamics. In recent years, TD-DCS technology has developed rapidly, including the proposal of various theoretical models, the verification of simulation and phantom experiments, as well as in vivo measurement of the human arm and head [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain highly sensitive TD-DCS measurement of deep dynamics, in addition to the above two factors, some other experimental factors (e.g., gate opening time and gate width, SD distance) should be considered in the experimental design and data analysis. Very recently, we have optimized some experimental factors on a realistic head model based on the simulation method, including SD distance and gate opening time and gate width [13]. The results showed that under acceptable input power of light, a high-contrast measurement of deep dynamic changes (e.g., cerebral blood flow caused by functional activation) can be achieved by selecting the optimal combination of SD distance(s) and time gate(s).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations